The Effect Of Post-Operative Care Education On Patients' Knowledge After Percutaneous Coronary Intervention (Pci) In The Icvcu Room At Dr. Iskak Tulungagung Hospital - Aprin Rusmawati; Alfian Fawzi; Nurul Hidayati (Universitas STRADA Indonesia, 2025)
Coronary heart disease is caused by the narrowing of blood vessels due to atherosclerotic plaque. Percutaneous Coronary Intervention (PCI) is used to improve myocardial perfusion. Nursing education is crucial in enhancing patient understanding, preventing non-compliance with treatment, and helping them maintain a healthy lifestyle while preventing complications. This study aims to determine the effect of post-operative Percutaneous Coronary Intervention (PCI) care education on the knowledge level of patients in the ICVCU Room at dr. Iskak Tulungagung Hospital. This study employed a quasi- xperimental method. The sample was selected using consecutive sampling, consisting of 30 respondents. The instruments used were questionnaires, leaflets, and educational videos. Data analysis was conducted using the Wilcoxon signed-rank test. The findings indicate that before the education was provided, most respondents had a moderate level of knowledge, with 19 respondents (63.3%). After the education, there was an increase, with the majority of respondents (63.3%) demonstrating good knowledge. The Wilcoxon Signed Ranks Test showed an Asymp. Sig. (2-tailed) value of 0.000, indicating a significant effect of education on increasing patient knowledge in the ICVCU Room at dr. Iskak Tulungagung Hospital.Improved understanding of post-PCI care plays a crucial role in reducing the risk of complications, such as bleeding at the puncture site or side effects from the prescribed medications